HIV Infection Increases the Risk of Incident Psoriasis: A Nationwide Population-Based Cohort Study in Taiwan. (15th August 2017) - Yen, Yung-Feng; Jen, I-An; Chen, Marcelo; Lan, Yu-Ching; Lee, Chun-Yuan; Chuang, Pei-Hung; Lee, Yun; Arthur Chen, Yi-Ming
Abstract : Background: HIV can cause an imbalance of T lymphocytes, which may contribute to the onset of psoriasis. However, the association of HIV with incident psoriasis has not been extensively studied. Objectives: The aim of this nationwide population-based cohort study was to determine the association of HIV with incident psoriasis. Methods: Since January 1, 2000, we identified adult people living with HIV/AIDS (PLWHA) from the Taiwan National Health Insurance Research Database. A control cohort without HIV infection, matched for age and sex, was selected for comparison. All patients were followed until December 31, 2012, and observed for the occurrence of psoriasis. The time-dependent Cox proportional hazards model was used to determine the association of HIV with incident psoriasis, while considering death as a competing risk event. Results: Of the 102, 070 patients (20, 294 PLWHA and 81, 776 matched controls), 248 (0.24%) had incident psoriasis during a mean follow-up period of 5.53 years, including 81 (0.40%) PLWHA and 171 (0.21%) controls. After adjusting for age, sex, and comorbidities, HIV infection was found to be an independent risk factor for incident psoriasis (adjusted hazard ratio, 1.80; 95% confidence interval: 1.38 to 2.36). Conclusions: The population of PLWHA is living longer; clinicians need to be aware of their higher risk of psoriasis.